Managing Obsessive-Compulsive Disorder through Utilizing Islamic Antidotes - Yankari, Ali Samaila; Maikamba, Musa A.; Hasan, Md. Mahdi; Jungudo, Ahmad Muhammad (Muslim Education Review, 2024)
Obsessive-compulsive disorder (OCD) is a prevalent mental health condition characterized by compulsive behaviors and irrepressible impulses. The treatment for this disorder is challenging due to its complex nature. It is occasionally linked to religious observances referred to as scrupulosity. This disorder exhibits a multitude of consequences. The manifestation of these intrusive thoughts and undesirable behaviors among students impede their ability to study efficiently and negatively impact their academic performance. Researchers and academics have put forth a range of pharmaceutical and psychological remedies and solutions for this catastrophic disorder. This research proposes potential Islamic strategies for resisting and curtailing the disorder. The research findings indicate that the Islamic antidote for managing OCD involves several spiritual and therapeutic practices such as dhikr (remembrance of God), tawakkul (trust in God), salah (prayer), du’a (supplication) and istighfar (seeking forgiveness). Additionally, individuals afflicted with this disorder, should employ strategies such as daily supplications, incantation (Al-uqyah Al-Sharʿiyyah) and efforts to prevent intrusive thoughts. The study effectively employed a descriptive methodology to conduct its examination.